Finding Wholes in the Metaverse: Posthuman Mystics as Agents of Evolutionary Contextualization - Bolger, Ryan K. (Religions, 2021)
The Metaverse is a pervasive expression of technological culture whose impact will be global. First, through knowledge, then through social, and now through geo-spatial, AI (the foundation of the Metaverse) will connect all entities on Earth through digital means thereby creating a three-dimensional informational and experiential layer across the world dubbed the Metaverse. The Metaverse has four characteristics: augmented reality, lifelogging, mirror worlds, and virtual reality. From the standpoint of Christian cultural engagement, a contextual theology has yet to be developed. In the work that follows, the Metaverse is engaged through a combination of contextualization and wholemaking from the standpoint of posthumanism and mysticism. The study focuses on evolutionary wholemaking as identified by Teilhard/Delio, while being guided by Bevans’ five (early) models of contextualization. The method of contextual wholemaking enables new ways of seeing, embracing, communing, complexifying, and creating within the four spheres of the Metaverse. After exploring the nature of the Metaverse in the first half of the paper, insights were gathered from the dialogue between contextual theology and culture and discussed in the second half of the paper.